STRATEGI CITY BRANDING OLEH PEMERINTAH DAERAH KABUPATEN SIAK DALAM PENINGKATAN DAYA TARIK PARIWISATA - Rusadi, Sylvina; Wedayanti, Made Devi (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2019)
City Branding is a promotion strategy to increase the attractiveness of tourism which is very popular lately, as evidenced by various regions in Indonesia trying to shape the character of their regional tourism so that it can be more easily recognized only through a term. The Siak Regency Government also utilizes City Branding as one of the promotion strategies in increasing the attractiveness of its regional tourism, namely through "Siak The Truly Malay" which has been patented through the Directorate of Copyright and Industrial Design of the Ministry of Law and Human Rights. From the various explanations above it can be seen that the Siak Regency Government held so many events that were carried out in an effort to attract tourism, but the Siak Regency Government needed to add events tourism that reflected the Malay culture because this destination City Branding not only attracted domestic tourists but also foreign tourists, because geographically Siak Regency is close to neighboring countries such as Malaysia and Singapore. Research conducted at the Siak Regency Tourism Office is very necessary to be carried out considering the City Branding Strategy "Siak The Truly Malay" has been launched and should be able to attract the interest of foreign tourists in particular. For that the Siak Regency Government needs to increase its tourist attraction in the area.